Economic growth in St. Vincent and the Grenadines (2001)
Identifies the sources of economic growth in St. Vincent and the Grenadines from 1978 to 1996. Suggests that to facilitate a higher rate of growth, policies, which increase total factor productivity growth will have to be pursued. Notes that among such policies are measures to develop and muture social capability.
Keywords: ECONOMIC GROWTH